Evaluasi Program Pembelajaran Bahasa Indonesia di SD Mutiara Harapan Islamic School - Ika Puspita Sari; Musringudin Musringudin (Jurnal Pendidikan Indonesia, 2022)
The implementation of learning plays an important role in determining the success of student learning. Teachers also greatly contribute to the success of learning success, because the role and competence of teachers affect the success of classroom management and student learning outcomes. Teachers must carry out evaluations for their students both individually and in class. The means of measuring self-efficacy and consumption of education is through the curriculum. Because what determines the activities of the educational process is determined through the curriculum. One of the goals of the institution is that students are expected to be able to communicate both using the national language, namely Indonesian and also able to communicate using English. Researchers want to know the knowledge and language skills of students, especially in communicating using the national language, namely Indonesian, because the time to speak Indonesian at school is less than the time to communicate in English. Not only that, the use of English is also used as the language of communication at home with the family. This research was conducted to realize the improvement of the quality of education and learning. In the evaluation of Indonesian language learning using a goal-oriented model (Goal Oriented Evaluation Model). This evaluation model uses goals as criteria to determine success. The conclusion from the context aspect of the Indonesian language learning program is that learning is formed based on applicable rules and as an answer to the school's desire to be able to realize one of the school's goals, namely "to be able to communicate using Indonesian well". From the recapitulation table the percentage of Indonesian language scores is already good above 70%, but for grades 1 and 2 it is at the lowest percentage level because grade 1 and grade 2 children are not able to think abstractly. Therefore, the learning process should be done face-to-face.